1989
DOI: 10.1111/j.1528-1157.1989.tb05326.x
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Clonazepam After Long‐Term Treatment

Abstract: Frequent unwanted side effects and development of tolerance are the main disadvantages of clonazepam (CZP) in long-term treatment of epileptic patients. A review of the literature shows that CZP tolerance more often appears in severe forms of childhood epilepsy (West and Lennox-Gastaut syndromes) than in other epileptic syndromes. We prospectively studied the consequences of CZP discontinuation in 40 consecutive children with difficult-to-treat epilepsies and multiple-drug therapy. The CZP was reduced stepwise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Except for the report of Specht et al (1989), reports have described only the occurrence of GTC status epilepticus. My study also showed development of a first GTC seizure and frequent attacks of non-GTC status epilepticus.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Except for the report of Specht et al (1989), reports have described only the occurrence of GTC status epilepticus. My study also showed development of a first GTC seizure and frequent attacks of non-GTC status epilepticus.…”
Section: Discussionmentioning
confidence: 90%
“…Abrupt discontinuation of clonazepam (CZP) can induce seizure exacerbation or status epilepticus (Browne, 1976), but only a few cases have been reported (Edwards and Eadie, 1973;Lund and Trolle, 1973;Edwards, 1974;Sechi et al, 1984;Sironi et al, 1984;Ghadirian et a]., 1987;Specht et al, 1989) and little is known about their clinical characteristics, including seizure symptoms, reason for rapid discontinuation of CZP, time lag from discontinuation to seizure exacerbation, and treatment. While widely recognized that abrupt CZP discontinuation should be avoided (Browne, 1978), it may occur in clinical practice because of side effects of CZP or other reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More severe intoxication is associated with runs of high-amplitude, intermittent rhythmic delta activity superimposed on a background of nearly Drug Effects on the Human Electroencephalogram 303 continuous slow activity of less than 4 Hz. 10,20 Other Antiepileptic Drugs As a general rule, the antiepileptic drugs (AEDs) reduce epileptiform activity, 21,22 although on occasion they can exacerbate EEG abnormalities and seizures. Little reactivity is elicited by stimulation.…”
Section: Antiepileptic Drugsmentioning
confidence: 99%
“…Of these, barbiturates and benzodiazepines are used as AEDs. Clonazepam is the most problematic drug in this respect [8] because of its high potential to produce withdrawal syndromes which cannot be safely avoided by stepwise withdrawal -as is possible with phénobarbital. As seizures are the most prominent symptoms of clonazepam withdrawal, it may be difficult to know to which of the two types of AED withdrawal syndromes the psychiatric symptomatology belongs.…”
Section: Withdrawal Syndromes With Psychiatric Symptomatologymentioning
confidence: 99%